An overview of existing criminological research on school violence and bullying behaviour: a review through secondary document analysis - Hesselink, Annika W. (Acta criminologica, 2017)
School violence is a socio-cultural occurrence and a concern for South Africa (as it is in many other countries) that justifies global attention. In South Africa, much has been written in the field of criminology on school violence and bullying behaviour. Existing criminological research from 2003 to 2013 was traced in order to establish the relevance of the content of these research projects in contrast to more recent occurrences of school violence and bullying behaviour as depicted in secondary sources. Hence, this article outlines the value of existing criminological research on school violence and bullying behaviour in relation to available contemporary secondary data (media reports). A qualitative approach was applied that is underscored by a research question. The research question aimed to establish whether dated criminological research on school violence and bullying behaviour is relevant and valuable to contemporary criminological understanding of the issue of school violence. This document analysis examined 11 criminological research endeavours against 25 media reports so as to establish whether there is value in criminological research for contemporary society. The findings suggest that both the criminological research and the media reports focused on the same themes with regard to school violence and bullying behaviour. The media reports covered a wide range of provinces in South Africa, while criminological research focused largely on the Gauteng Province and on Lesotho. The criminological research studies focused on limited physical abuse, while the media reports reflected on brazen violence between learners. While criminological research delivered extensive consequences of bullying and violent behaviour; media reports outlined and elaborated more on the reasons for violence in schools and bullying behaviour.